Perilaku Individu Dalam Organisasi - Ansori, Ansori; Rosa Indah; Suwandi, Suwandi; Inda Salsabila; Firmansyah, Firmansyah (Pusat Riset dan Inovasi Nasional, 2024)
Behavior includes various human activities, such as walking, talking, crying, laughing, working, studying, writing, reading, etc. Behavior can also be interpreted as a person's reaction or response to external stimuli, including those originating from the organizational environment. Organizations need to deeply understand the characteristics, attitudes and behavior of each individual. It is important to remember that humans are basically unequal due to differences in biological background, education, and various other factors that shape individual characteristics. This diversity of individuals is an important aspect that should not be overlooked. This article examines individual behavior in organizations with a variety of approaches to understanding human nature, including cognitive, complacency, confirmation, and psychoanalytic approaches.